Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 5 - Logarithmic, Exponential, and Other Transcendental Functions - 5.4 Exercises - Page 352: 42



Work Step by Step

$y=x^2e^{-x}$ $u=x^2$ $u’=2x$ $v=e^{-x}$ $v’=-e^{-x}$ $y’=(2x)(e^{-x})-(x^2)(e^{-x})$ $=(x)(e^{-x})(2-x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.